The Implementation of Government Regulation No. 49 of 2025 in Establishing the 2026 Regency/City Sectoral Minimum Wage by the Governor of West Java - Mimin Ida Nurjanah; Muhammad Abas; Yuniar Rahmatiar (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The enactment of Government Regulation Number 49 of 2025, which re-established the authority to determine Regency/Municipal Sectoral Minimum Wages (UMSK), has sparked considerable legal and policy debate concerning its implementation in West Java Province. This study aims to examine the implementation of the governor’s authority in determining the 2026 UMSK and to assess its conformity with administrative law principles and applicable laws and regulations. This study adopts a normative juridical approach, employing statutory and conceptual analyses, complemented by empirical evidence obtained through semi-structured interviews. The legal materials consist of primary legal sources in the form of legislation and secondary legal. The findings indicate that the implementation of UMSK determination in West Java has not fully complied with normative provisions, particularly regarding the phrase “based on recommendations,” which in practice is not consistently used as the primary reference by the governor. Furthermore, non-juridical factors such as economic interests and political dynamics also influence the policy, resulting in potential industrial conflicts and legal uncertainty. Therefore, it can be concluded that the implementation of the governor’s authority in determining the 2026 UMSK has not fully reflected the principle of legality and the general principles of good governance.